2023
DOI: 10.1002/cjoc.202200799
|View full text |Cite
|
Sign up to set email alerts
|

N, S‐Doped Carbon Dots as Additive for Suppression of Zinc Dendrites in Alkaline Electrolyte

Abstract: Comprehensive Summary The severe dendrite growth on zinc anode in alkaline electrolyte brings great challenge to the development of zinc‐based batteries. It is a simple and effective strategy to inhibit zinc dendrite formation by introducing additives into the electrolyte. In this study, N, S‐doped carbon dots (TU‐CQDs) were synthesized and used as additives to regulate zinc deposition in a typical KOH electrolyte. The experimental and three‐dimensional transient nucleation model disclosed that the special fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Whereas, these critical scientific problems are still very open to be investigated, and more endeavors should be paid to build an explicit relationship between the battery performance and physicochemical properties and nanostructure of CDs; 3) in line with literature Reproduced with permission. [109] Copyright 2023, Wiley-VCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, these critical scientific problems are still very open to be investigated, and more endeavors should be paid to build an explicit relationship between the battery performance and physicochemical properties and nanostructure of CDs; 3) in line with literature Reproduced with permission. [109] Copyright 2023, Wiley-VCH.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showcased TU‐CQDs were more advantageous than that of A‐CQDs as the additive in achieving dendrite‐free Zn interface during long‐term electroplating processes ( Figure ). [ 109 ]…”
Section: Applications Of Cds In Zn‐air Batteriesmentioning
confidence: 99%
“…The stability of the Zn anode is hindered by dendrite formation, which punctures the separator and induces short circuits. [15][16][17][18] In the initial plating process, Zn 2+ near the electrode surface is preferentially reduced and inclined to form small protuberances on the Zn foil. During further plating, the protuberances attract the deposition of more Zn 2+ as a result of the "tip effect".…”
Section: Fundamentals Of Zibsmentioning
confidence: 99%
“…Several studies have shown that N, F, P, S, Se, B and their conjugate doping significantly affect the emission properties of CDs. [ 44‐45 ] In particular, for N atoms, with their electron donor status, doping N in CDs usually leads to a red‐shift of PL emission. For example, N‐CDs synthesized with carbonation and polymerization procedures showed significantly higher PL intensity and up to 56.1% QY compared to undoped CDs.…”
Section: Preparation Of Deep‐red To Near‐infrared Cdsmentioning
confidence: 99%